2019
DOI: 10.1093/zoolinnean/zlz002
|View full text |Cite
|
Sign up to set email alerts
|

A molecular phylogeny for the Pacific monitor lizards (Varanus subgenus Euprepiosaurus) reveals a recent and rapid radiation with high levels of cryptic diversity

Abstract: We provide a geographically well-sampled, time-calibrated molecular phylogeny for the Pacific monitor lizards (Varanus: subgenus Euprepiosaurus) based on ND4 and 16S rRNA mitochondrial DNA sequences. Three well-supported clades, or species groups, are retrieved: the Varanus doreanus Group, the V. jobiensis Group and the V. indicus Group. The subgenus is estimated to have originated in the Mid-Miocene, but extant lineage diversification dates from the Late Miocene and Pliocene. A rapid and widespread radiation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 45 publications
4
21
0
Order By: Relevance
“…All other species in this group are endemic to single islands or smaller archipelagos in the Moluccas, Melanesia and-as demonstrated here-in Palau, the Western Carolines and the Mariana Islands. Molecular-dating techniques have shown that expansion and diversification of this clade happened during the Pleistocene and that differentiation and speciation has been rapid on islands isolated enough for gene flow to be minimal or non-existent [23].…”
Section: Species Recognitionmentioning
confidence: 99%
See 3 more Smart Citations
“…All other species in this group are endemic to single islands or smaller archipelagos in the Moluccas, Melanesia and-as demonstrated here-in Palau, the Western Carolines and the Mariana Islands. Molecular-dating techniques have shown that expansion and diversification of this clade happened during the Pleistocene and that differentiation and speciation has been rapid on islands isolated enough for gene flow to be minimal or non-existent [23].…”
Section: Species Recognitionmentioning
confidence: 99%
“…However, as highly similar mitochondrial haplotypes can often be found in geographically distant populations (e.g. the islands of Karkar, Wewak and Fergusson (figures 3 and 4), and single locations often have a mix of different haplotypes (figures 3 and 4 [23]), it seems likely there has been incomplete lineage sorting among geographically distant but recently isolated populations of V. indicus. In contrast, between the insular populations currently recognized as species (i.e.…”
Section: Species Recognitionmentioning
confidence: 99%
See 2 more Smart Citations
“…These and other Micronesian populations have long been included under the name Varanus indicus and reported to have been introduced during the Japanese administration. However, recent molecular and morphometric studies revealed that monitor lizards from western Micronesia form a distinct clade (and two separate species) and appear to have colonized those islands by natural dispersal several hundred thousand years ago rather than by more recent human-mitigated introduction (Weijola et al 2019(Weijola et al , 2020. Weijola et al (2020) Early reports of monitors and descriptions of lizards probably referring to monitors in the FSM predate the Japanese administration and suggest a longer history of Varanus in this region than is generally thought: de la Corte (1875) mentioned "iguanas" on Pohnpei, Cabeza Pereiro (1895) identified a large lizard that he saw on Pohnpei during the 1890s as a monitor, and Lesson (1839 as translated by Ritter and Ritter 1982:48) reported seeing a gecko and two other kinds of lizards on Kosrae during 5-15 June 1824, a greencolored species [probably Lamprolepis smaragdina] and one with a blue tail and golden stripes on its back [almost certainly Emoia sp.…”
Section: Monitor Lizards In Micronesiamentioning
confidence: 99%